The Association of a Number of Anatomical Factors with the Success of Retrograde Intrarenal Surgery in Lower Calyceal Stones - Sari, Sercan; Ozok, Hakki Ugur; Topaloglu, Hikmet; Cakici, Mehmet Caglar; Ozdemir, Harun; Karakoyunlu, Ahmet Nihat; Senturk, Aykut Bugra; Ersoy, Hamit (Urology Journal, 2017)
Purpose: To determine anatomical factors affecting Retrograde Intrarenal Surgery (RIRS) success in the treatment of renal lower calyx stones. Materials and methods: The results of patients were evaluated retrospectively. The patients who have preoperative intravenous urography (IVU) and computed tomography (CT) were divided into two groups as successful (S)(N=103) and unsuccessful(U) (N=29). The anatomic characteristics such as infundibulopelvic angle (IPA), infundibular length (IL), infundibular width (IW) and pelvicaliceal height (PCH) values were compared among two groups. Results: Mean patient age was 47±13.6 years in group S and 49.5 ±11.9 years in group U. The mean stone size was 10mm (6-54mm) in group S and 19mm (8-45mm) in group U (P < .001) Mean IPA was 85.8 ±16.9 degree in group S versus 54.7 ± 11.5 degree in group U. The mean PCH was 1.9cm (0.5-4cm) in group S versus 2.3cm (0.7-3.9cm) in group U. The mean IL were 2.7 ± 0.8 cm and 3.2±0.7cm in group S and group U, respectively. The mean IWs were 0.7 cm (0.2-2.3cm) and 0.7cm (0.3-2) in group S and group U, respectively. The differences were statistically significant for IPA, PCH, IL (P < .05) while was not statistically significant for IW (P > .05). After multivariate analyses, PCH, IPA and stone size were statistically significant factors. Conclusion: In our study we found that IPA, PCH and stone size were significant anatomical factors affecting RIRS success in the treatment of renal lower calyx stones. The patients whose IPA, PCH and stone size valuables are unsuitable, may need multiple RIRS sessions or additional treatment modalities.